Spotlight on pembrolizumab in the treatment of advanced melanoma - Rajakulendran T; Adam DN (Dove Medical Press, 2015)
Thanashan Rajakulendran,1 David N Adam2 1Department of Medicine, Division of Dermatology, Postgraduate Medical Education, 2Department of Medicine, Division of Dermatology, St Michael’s Hospital, University of Toronto, Toronto, ON, Canada Abstract: Metastatic melanoma is an aggressive cancer with a poor prognosis. Many approved therapies often do not achieve durable responses in patients. This underscores the need for novel therapeutic strategies. Recruiting a robust immune response is an important antineoplastic treatment strategy. Immune checkpoints offer a molecular target for modulating the immune response and a promising therapeutic target in metastatic melanoma. Here we discuss the recent approval of pembrolizumab by the US Food and Drug Administration for the treatment of metastatic melanoma and its impact on future management of the disease. Keywords: pembrolizumab, melanoma, immune checkpoint, PD-1, PD-L1